Design data handler in wireless sensor network: article - Abd Ghani, Nurul Syuhada (2009)
The development wireless sensor network (WSN) is to monitor indoor air quality of laboratories. The architecture for WSN as indoor air quality monitoring system can be divide into two stages which is architecture for sensor nodes and GUI development for base station (data handler). This project just concentrates on GUI development for base station. In this project, WSN system has 3 sensor nodes which are placed in different laboratories. The sensor node delivers the indoor air temperature and relative humidity for every hour until 24 hours of monitoring to base station. Data handler act as base station to collect message or information that relay from sensor nodes through transceiver. Base monitoring is the last part of WSNs which is to analyze all information and handle the event data from sensor node. The result of monitoring is use to determine the dew point and humidex value can be predicted as a range and degree of comfortable.